Effect of Membrane Structure on Blood Compatibility for Polyethersulfone Hollow Fiber Membrane - Shao, W.; Wang, H.T.; Wang, L.; Zhao, B.; Zhang, Z.H.; Guo, X.F. (Asian Journal of Chemistry, 2014)
In this study, polyethersulfone membranes with four types of structures, which were double finger structure (PES-DF), single finger structure (PES-SF), compact sponginess structure (PES-CS) and loose sponginess structure (PES-LS), were obtained by changing the additives and spinning techniques. Effect of the polyethersulfone membranes' structure on its blood compatibility was investigated by the experiments of water contact angle, water adsorption, bovine serum albumin adsorption and blood clotting time. All results showed that polyethersulfone membranes with sponginess structure had better blood compatibility than polyethersulfone membranes with finger structure. As for the polyethersulfone membranes with sponginess structure had better blood compatibility than double finger structure.